2009
DOI: 10.1017/s1049023x0000724x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Workplace Violence in Paramedics

Abstract: Introduction: The majority of research that has explored workplace violence has focused on establishing the prevalence of violence in different settings. In general, there is a paucity of research that explores factors that may predict or increase the risk of experiencing violence in the workplace. Objective: The aim of this research was to determine predictors of violence for paramedics. Methods: A questionnaire was developed that focused on paramedics' experiences with six forms of violence: verbal abuse, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 20 publications
2
38
0
6
Order By: Relevance
“…In international studies, as in our study, paramedics and EMTs often appear to be exposed to violence among the pre-hospital personnel too (11,12). Koritsas et al (12) reported that the professional skills of a paramedic, his receiving the call on the phone, and his weekly contact hours with the patients are actually risk factors in the exposure to verbal violence.…”
Section: Discussionsupporting
confidence: 59%
“…In international studies, as in our study, paramedics and EMTs often appear to be exposed to violence among the pre-hospital personnel too (11,12). Koritsas et al (12) reported that the professional skills of a paramedic, his receiving the call on the phone, and his weekly contact hours with the patients are actually risk factors in the exposure to verbal violence.…”
Section: Discussionsupporting
confidence: 59%
“…16 Because longer working hours mean more frequent interaction with patients, the risk of verbal abuse might increase. 17 Managers with longer work experience might be at high risk for verbal abuse, because they often assume responsibility and take on the task of dealing with patients and their relevant complaints. 11 …”
Section: Risk Factors Of Verbal Abusementioning
confidence: 99%
“…A lot of studies reported that female gender is a risk factor of sexual harassment. 17,19 Safety Factors of Workplace Violence Adjusted odds ratios of operation departments, and obstetrics and gynecology wards, perinatal wards, or NICU were common safety factors for each type of workplace violence. Usually, the patients in operation rooms cannot talk or move a finger carelessly during the surgery.…”
Section: Risk Factors Of Sexual Harassmentmentioning
confidence: 99%
“…In contrast with the findings from Boyle et als study, Petzall found no correlation between gender, experience or position on the likelihood of adverse occupational health events occurring (3,4). Other studies examining the experiences of paramedics in the prehospital environment suggest that verbal abuse (5), occupational violence (6)(7)(8)(9)(10)(11)(12)(13)(14) and sexual harassment (5) may occur. As paramedic students work in the same environment as the qualified paramedics surveyed, it stands to reason that students are exposed to similar events.…”
Section: Literature Reviewmentioning
confidence: 86%